Spinal Muscular Atrophy II/III and Feeding Problems - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at Kaohsiung Medical University Hospital, Taiwan studied the prevalence and risk factors of feeding and swallowing problems in 108 genetically confirmed patients with types II and III spinal muscular atrophy (SMA), age range 3-45 years, 60 with type II and 48 with type III.